(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article is devoted to the theoretical study of issues related to the process of formation of geoecological culture through school geography education. The authors, expressing the opinions and comments obtained as a result of their scientific research, tried to determine the prospective study vector of the problem.